EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI KEPEGAWAIAN DALAM MANAJEMEN PNS DI KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA LAMPUNG - Putri Rachma Sholeha (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
The use of an information system is a must in facing complex organizational challenges. Utilization of the Personnel Management Information System aims to improve work efficiency and decision making related to civil servant management. The purpose of this study was to determine the effectiveness of the use of the Civil Service Administration Information System (SIMPEG) for Civil Servants in the Regional Office of the Ministry of Law and Human Rights in Lampung and the obstacles to its use. The method used in this study is naturalistic qualitative, researchers will collect data in a natural way through interviews with key informants, direct field observations and researching related documents. The results showed that the use of Administrative Information Systems in PNS Management at the Regional Office of the Ministry of Law and Human Rights Lampung is still quite effective because it fulfills the components of measuring the effectiveness of information systems in the form of security (confidentiality, availability, integrity) and output. The obstacles encountered when using the Civil Service Information System (SIMPEG) to meet the needs of civil servant management were that corrupt files were found due to application errors, incomplete data, leadership intervention in making decisions that ruled out the information presented by SIMPEG for consideration, and the internet network is unstable to access SIMPEG so that the staffing service process is obstructed. Keywords : Effectiveness; Civil Servant Management; SIMPEG.